PERANAN GURU PENDIDIKAN AGAMA ISLAM MELALUI METODE KITABAH DALAM MENINGKATKAN MINAT BACA SISWA MADRASAH IBTIDAIYAH - Hendra SH (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
This study examines literacy activities in the Kitabah learning method in Islamic subjects in Madrasah Ibtidaiyah’s students. The Kitabah method is an educational method through writing and reading activities. The Kitabah method is considered an effective method in Arabic enrichment. Still, the Kitabah method is a learning strategy that relies on writing activities and the ability to describe reading comprehensively. The role of the Islamic Religious Education teacher encourages students to analyze and write the text well. This method has been used in traditional Islamic learning, effectively increasing students' interest in reading. Students of Madrasah Ibtidaiyah in Islamic subjects must direct students to read Islamic texts. This is one of the important parts of Islamic Religious Education in the form of 1) a role in increasing interest in reading, 2) socialization of classical Islamic texts to students from an early age, and 3) adding active Islamic teaching and learning activities between students and teachers. The subject of this study is Teachers and Students of Madrasah Ibtidaiyah. Research is qualitative by collecting data from literature studies of related research. This research is expected to be a source of study of Islamic Religious Education in improving literacy culture at the Ibtidaiyah Madrasah level.